2011
DOI: 10.1016/j.jfoodeng.2011.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aqueous ozone, blanching and combined treatments on microbial load of red bell peppers, strawberries and watercress

Abstract: a b s t r a c tThe effectiveness of ozone in aqueous solution treatment on microbial inactivation was studied for three combinations microorganism/food: Listeria innocua/red bell peppers (artificially inoculated), total mesophiles/strawberries, and total coliforms/watercress, with two concentrations (0.3 and 2.0 ppm). Blanching treatments (50-60°C) were also individually applied and in combination with ozone, for studying possible synergistic effects. In relation to ozone treatments, the highest microbial redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0
9

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 22 publications
1
54
0
9
Order By: Relevance
“…In the second assay, açai berries were blanched at 90 °C and cooled with different aqueous sources (Figure 1). The ratio between the sample mass and the volume of water used in all test solutions for açai berries treatment was 40 g.L -1 (12). The recovered microbial enumeration from berries of two assays was performed before decontamination treatments (N 0 ).…”
Section: Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the second assay, açai berries were blanched at 90 °C and cooled with different aqueous sources (Figure 1). The ratio between the sample mass and the volume of water used in all test solutions for açai berries treatment was 40 g.L -1 (12). The recovered microbial enumeration from berries of two assays was performed before decontamination treatments (N 0 ).…”
Section: Treatmentsmentioning
confidence: 99%
“…The efficiency of chlorination can be influenced by organic matter present in water, as well as insufficient cooling, exposure to air or light, or a combination of these three factors [11]. Ozone (O 3 ) is one of the most powerful oxidizing agents (2.07 mV), effective for inactivation of Gram-negative and Gram-positive bacteria, viruses and yeasts, including sporulated forms [12], and protozoan cysts [13]. Studies have shown that treatment with ozonated water extends the shelf life of various food products, increasing quality and food safety [14; 15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several studies have shown that its use presents low potential with regard to changes in the sensory characteristics of food, which expands the possibilities for its use (USEPA, 1999;WHANG et al, 2004;ALEXANDRE et al, 2011;MUKHOPADHYAY;RAMASWAMY, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Application of minimal thermal processing such as hot water blanching is a better option to reduce the initial microbial flora [3] associated with the raw sprouts of legumes, and to preserve the natural color and the appearance of legume sprouts. Also it has been reported by many authors that, blanching not only reduce the initial microbial load but also improve the quality of fresh product but also it retains physical quality during low temperature storage while minimize the losses of nutrients as it is a mild heat treatment.…”
Section: Introductionmentioning
confidence: 99%